PENDIDIKAN AGAMA ISLAM MENGGUNAKAN METODE WUDHU UNTUK MENANGGULANGI KECEMASAN PADA LANSIA - Siti Maimunah; Rusdianingseh; Nety Mawarda Hatmanti; Nunik Purwanti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Anxiety is one of the psychological problems commonly experienced by the elderly due to physical changes, limitations in activities, and feelings of loss of social role. Islamic Religious Education (PAI) plays an important role in guiding the elderly to gain inner peace through spiritual approaches and worship practices. One simple method that has a spiritual as well as psychological dimension is ablution. In Islam, ablution not only functions as a valid condition for prayer, but also as a means of purification of the mind and body. The activity of washing the limbs with water that is done with full awareness is believed to be able to provide a relaxation effect, reduce anxiety, and increase peace of mind. This community service activity was carried out in the elderly community of Karangrejo, Surabaya, with the aim of increasing the elderly's understanding of the spiritual meaning of ablution while practicing it as a simple form of therapy to reduce anxiety. The implementation method includes counseling, ablution practice demonstrations, and spiritual experience reflection sessions. The results of the activity showed an increase in participants' knowledge about the meaning of ablution, an increase in the practice of ablution with solemnity, and positive testimonials from participants regarding the reduction of feelings of anxiety after performing ablution routinely. This program proves that PAI based on worship practices can be a simple and effective strategy to improve the mental health of the elderly.